Anti-fatigue Effects of Santé Premium Silver Perch Essence on Exhaustive Swimming Exercise Performance in Rats - Chen, Chung-Yu; Yuen, Hei-Man; Lin, Chung-Chi; Hsu, Chi-Chieh; Bernard, Jeffrey R.; Chen, Ling-Ni; Liao, Yi-Hung; Tsai, Shiow-Chwen (Frontiers in Physiology, 2021)
Aim: Fish soup is a traditional Chinese food usually offered as a healthy supplement to elders, pregnant women and persons who just had surgery. Silver perch (Santé premium silver perch essence, SPSPE) extract contains various quality proteins, collagen, minerals, trace elements, and branch chain amino acids (BCAA) that could help individuals recover from exhaustion and control body weight. However, there are very limited studies exploring the effects of fish extracts on exercise performance and fatigue, and relevant physiological mechanisms. Therefore, the purpose of this study was to investigate the effects of chronic SPSPE administration on exhaustive exercise performance. Method: Male Wistar rats weighing around 250 g were divided into 4 groups: Control, 1X SPSPE (6.2 ml/kg), 2X SPSPE (12.4 ml/kg) and 5X SPSPE (31.0 ml/kg). Rats were administrated SPSPE by oral gavage feeding every day for 33 days. Their body weight were measured every week. Before and after the exhaustive swimming test, the blood was collected for circulating lactate, glucose, ammonia, hormones, and myoglobin analysis. Rats were sacrificed after performing an exhaustive swimming exercise test. The liver tissues were collected for glycogen content and H&E staining. Results: After the administration of 1X and 5X SPSPE, swimming fatigue was significantly delayed (p = 0.024). There was no difference in the hormone plasma level between the control and SPSPE groups. The induction of plasma corticosterone and TBARS by exhaustive swimming exercise could be decreased by SPSPE administration. The increased plasma myoglobin concentration from exhaustive swimming exercise was weakened by SPSPE supplementation. The higher glycogen sparing contained in liver tissue was observed in SPSPE-treated groups (p < 0.05). Conclusion: SPSPE could efficiently delay swimming fatigue through sparing of liver glycogen and attenuation of plasma TBARS, myoglobin induction by exhaustive exercise. Our findings provide a scientific-based fundamental information and better understanding for developing a fish extract-based anti-fatigue supplement.